PENINGKATAN PERSEN EKSTRAKSI PROSES PELINDIAN EMAS DAN PERAK MENGGUNAKAN VARIASI TEKNIK PENINGKATAN OKSIGEN TERLARUT SPARGER LANCE, PEROXIDE INJECTION DAN HIGH SHEAR REACTOR - Ramadhan, Dikri Fajar; Hutabarat, Imelda Eva Roturena; Raja, Denny Lumban; Sulaeman (Jurnal Teknologi Mineral dan Batubara, 2024)
Cyanidation leaching has become the most intriguing technique for extracting gold and silver. In the gold and silver cyanidation process, PT Indo Muro Kencana (IMK) implements three (3) dissolved oxygen (DO) enhancement techniques. The concentration of DO typically becomes the limiting factor in the gold cyanidation process. The use of a pressurized system can also increase the DO concentration in water. Oxygen injection techniques with a sparger lance (standard/STD), peroxide injection (PRX), and high shear reactor (Aachen assisted leach/AAL) are employed to optimize the cyanidation process due to the increasingly complex characteristics of the processed ore since 2021. The use of a high shear reactor is the latest technique implemented since April 2022, following the previous implementation of peroxide injection and sparger lance by PT IMK. The objective of this study is to determine the extraction percentage and its stability in producing extraction percentages with different ore compositions. The oxygen used for each technique is the same, approximately 548 kg/hour flow rate, 90%-93% purity, and 4-6 KPa pressure. A series of leach tests are conducted to observe the extraction percentage of gold and silver. Based on the conducted tests, the reactor high shear technique yields the highest extraction percentages for gold and silver, namely 97.06% and 82.82% respectively. Leaching with the high shear reactor technique resulted in a higher percent extraction stability than the leaching process using the other two techniques.